GAME THEORY AND MARKOV CHAIN ANALYSIS OF THE DISPLACEMENT OF SHOPPING MALL VISITORS IN SURAKARTA CITY - Rizkita, Nabiella Zahra; Sutanto, Sutanto; Kurdhi, Nughthoh Arfawi (PATTIMURA UNIVERSITY, 2025)
The era of globalization has led to changes in social patterns and lifestyles. With these changes, shopping malls were built to fulfill the community’s needs. This study aims to analyze the displacement of visitors in three shopping malls in Surakarta City, namely Solo Paragon Mall, Solo Grand Mall, and Solo Square, using game theory and the Markov chain. Game theory is used to determine the optimal strategy of each shopping mall based on six indicators of visitor satisfaction, namely product diversity, presence of transportation modes, distance, price, facilities, and services. Saddle points are obtained by pure strategy. The calculation results with the game theory method resulted in three competitions. The first competition between Solo Paragon Mall and Solo Grand Mall obtained the optimal strategy of Solo Paragon Mall is product diversity. At the same time, Solo Grand Mall is the existence of transportation modes. The second competition between Solo Paragon Mall and Solo Square obtained the optimal strategy of Solo Paragon Mall, which is product diversity, while Solo Square's optimal strategy is service. Lastly, the third competition, Solo Grand Mall and Solo Square, obtained the optimal strategy of Solo Grand Mall is the presence of transportation modes and Solo Square is service. Markov chain is used to calculate the transition probability of visitors and steady state, which shows that Solo Paragon Mall is more desirable with a steady state probability of 0.4459, followed by Solo Square 0.3584 and Solo Grand Mall 0.1957. The results of this study can help shopping malls evaluate and improve their strategies to increase loyalty and attract new visitors.